Color-tunable electroluminescent polymers by substitutents on the poly(p-phenylenevinylene) derivatives for light-emitting diodes - Jin, SH; Kang, SY; Yeom, IS; Kim, JY; Park, SH; Lee, K; Gal, YS; Cho, HN (AMER CHEMICAL SOC, 2002)
Color tunable electroluminescent polymers, poly[2-{4'-[(3",7"-dimethyloctyl)oxylphenoxy}-1,4-phenylene-vinylene] (p-DMOP-PPV), poly[2-{3'-[(3",7"-dimethyloctyl)oxy]phenoxy}-1,4-phenylenevinylene} (m-DMOP-PPV), poly[2-{2'-[(3",7"-dimethyloctyl)oxylphenoxy}-1,4-phenylene vinylene] (o-DMOP-PPV), and poly[2-{4'-[(3",7"-dimethyloctyl)oxylphenoxyl-1,4-phenylenevinylene]-co-2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylenevinylene] (p-DMOP-PPV-co-MEH-PPV) were synthesized by the Gilch polymerization, and their electrooptical properties were characterized. The emission colors can be tuned by moving the bulky substitutents from the para to the ortho position in the phenoxy side group along the pi-conjugated polymer backbone. External photoluminescent (PL) quantum efficiencies of the present polymers are four or five times larger than that of MEH-PPV. Light-emitting diodes (LED) with the ITO/PEDOT/polymer/Al configuration were fabricated by using those polymers. The turn-on voltage of the p-DMOP-PPV-co-MEH-PPV (3:7) was found to be 1.8 V and it is lower than those of o-, m-, and p-DMOP-PPV and MEH-PPV. The LED performance of the p-DMOP-PPV-co-MEH-PPV was found to be improved with various feed ratios of MEH-PPV content as compared with the devices using pure p-DMOP-PPV or MEH-PPV. The maximum brightness and luminance efficiency of the present polymers were 7000 cd/m(2) and 1.0 cd/A at 10 V, respectively.
Keywords: BROMIDE)